The Masculinization of Guppy Poecilia reticulata (Peters. 1859) Using Tribulus terrestris (Linnaeus, 1753) Extract Through Immersion of Pregnant Female Broodstock and Larvae - Sarida, Munti; Mahadinata, Marto; Kembaren, Jerry Suranta Sembiring; Elisdiana, Yeni; Fidyandini, Hilma Putri (Journal Omni-Akuatika, 2025)
The technology of sex reversal in guppy (Poecilia reticulata) cultivation is a way to produce monosex males through masculinization techniques. Utilization of Tribulus terrestris (ETT) extract can be used for a lower cost and is environmentally friendly. This study aims to examine the effect of giving Tribulus terrestris extract on masculinization of guppies by immersing pregnant female mothers and in the larval stage. The research design for sex reversal with pregnant sows used a completely randomized design (CRD) and for guppies in larval stages used a randomized block design (RBD). The treatment for immersion with pregnant mothers was K- without ETT and 17alpha-methyltestosterone, K+ treatment with 17alpha-methyltestosterone 500 microgram/L, P1 with 5 mg/L ETT dose, P2 with 10 mg/L ETT dose, and P3 with 10 mg/L ETT dose. ETT 15 mg/L. The treatment for immersion in the larval stage was K- without ETT and 17alpha-methyltestosterone, K+ treatment with a dose of 17alpha-methyltestosterone 8 mg/L, P1 with an ETT dose of 2.5 mg/L, P2 with an ETT dose of 5 mg/L, and P3 with an ETT dose of 10 mg/L. Tribulus terrestris extract has an effect on masculinization of guppies by immersing pregnant sows with the best treatment P3 at a dose of 15 mg/L. Then, the growth performance of guppy fish larvae was affected by the administration of Tribulus terrestris extract, but there was no difference in the dose.